Executive's guide to personal security - Katz, David S. 1960-; Caspi, Ilan (Wiley, 2020)
"This book provides detailed information relative to all aspects of personal security issues facing Americans and other "industrialized nations" nationals who are living and working abroad as well as corporate security issues. It will include situational awareness, counter-surveillance, physical security, principles of route selection, technical security systems, hostage situations, emergency planning, hotel and room selection, armored products, communications, bomb threats, evacuations and local criminal hazards to name just a few. This new edition will include a chapter on active shooter response (corporate and individual), more detail concerning protecting IP and computers/smart phones etc., and additional information on planning for emergencies at home and the office as well. American and other "industrialized nations" interests have long been an attractive target for those who would seek to further political and economic goals through violence. This is even more so after the attacks on 9/11 and the subsequent U.S. military action in various parts of the world. In addition, violent crimes, such as kidnapping have become almost an industry in certain parts of the world. This book will be an invaluable source of information for those most at risk and will allow the reader to make the right decisions in regard to his or her personal safety"--
Includes index. - Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Executives -- Protection; Executives -- Crimes against -- Prevention; Business travel -- Safety measures; Violence in the workplace -- Prevention; Corporations -- Security measures; Office buildings -- Security measures; Emergency management; Private security services; Voyages d'affaires; Sécurité; Mesures; Sociétés; Sécurité; Mesures; Immeubles de bureaux; Sécurité; Mesures; Services privés de sécurité; Business travel; Safety measures; Corporations; Security measures; Executives; Crimes against; Prevention; Executives; Protection; Office buildings; Security measures; Violence in the workplace; Prevention